Ejercicios excéntricos en el tratamiento Fisioterapéutico de la Tendinitis del manguito rotador. Centro de Salud Salcedo, 2018-2019 - Viteri Fiallos, Mayra Patricia (2019)
The project research project eccentric exercises in the physiotherapeutic treatment of rotator cuff tendonitis. At the Salcedo Health Center, 2018-2019 the main objective is to determine the effects of eccentric exercises in the physiotherapeutic treatment of patients with rotator cuff tendinitis through the Daniels test, goniometry and EVA scale. The Salcedo Health Center serves approximately 70 patients per day in the area of Physical Therapy, rotator cuff tendinopathy is one of the most common injuries in the area, 40% of patients for those who are attended in it, having this pathology, 25 patients have been selected under detailed criteria of inclusion and exclusion, patients who are in the stage of muscle strengthening and do not present chronic pain. The rotator cuff is a group of muscles made up by the supraspinatus, infraspinatus, subscapularis and minor round, are responsible to give motion and stability to the shoulder The eccentric exercises helped to increase muscle strength, reduce pain, this is part in order prevent future injuries in the shoulder, this type of exercises is recommended to work in tendinopathies in their initial phases of strengthening thus helping to an optimal recovery. The results obtained showed a higher incidence of rotator cuff tendinitis in women than in men, for the life of the project was 8 weeks with 5 sessions per week, initially measuring pain intensity by means of the EVA scale and muscle strength by the Daniels test.